PROGRAM PEMBENTUKAN DAN PENINGKATAN KAPASITAS PETANI PESISIR DOMPAK LAUT SEBAGAI PEMBERDAYAAN MASYARAKAT PESISIR - Horista, Klemensia Michelle Novely; Rahayu, Ety (Jurnal Pembangunan Manusia, 2022)
Indonesia as a maritime country has many coastal community groups. But unfortunately, the various efforts to develop the blue economy have not been able to improve the welfare of these community groups. Most of them choose to depend on the fisheries and tourism sectors, even though Indonesia's marine potential is vast and there is much that can still be developed. Coastal communities are not aware of the climate crisis that is getting worse and can threaten the security of the environment where they live. Based on this, the CarbonEthics Foundation seeks to be a solution by prioritizing training and education to save the earth while empowering coastal communities. This study further examines one of its newest programs, namely the Capacity Building and Capacity Building Program for the Dompak Laut Coastal Farmers group. The research was conducted with a qualitative approach and descriptive method with data collection in the form of in-depth interviews and literature studies. The results of the study found that this program not only provides technical training but also education to increase awareness regarding marine natural conditions, as well as assistance and supervision which is planned to be carried out for three years. Part of the implementation and planning of this program is in accordance with the theory of stages of empowerment. The stage of formulating the action plan was not appropriate because the CarbonEthics Foundation formulated and determined programs and activities without the participation of the community or program participants. However, this stage is a cyclical process. In addition, in less than half a year, program participants have benefited from their new abilities by getting an 83% increase in income. This finding supports the foundation program as an empowerment effort. With a program like this, coastal communities will then become more empowered and able to compete with their new capabilities.